Foreign direct investment, exports and imports in Mexico - Penélope Pacheco-López (University of Kent, Department of Economics, 2004)
This paper analyses the liberalisation of foreign direct investment (FDI) in Mexico since the late-1980s, and its relationships with exports and imports. Such a process has eased the access of multinational corporations (MNCs) to the country, which has promoted exports. However, it has also resulted in a higher import content and the displacement of local firms, which has limited Mexico's economic development through the balance of payments constraint. The analysis is supported by the existence of linkages -bi-directional Granger causality- between exports, imports and FDI.
Keywords: F14; F21; F23; O1; 330; Foreign Direct Investment-Liberalisation; Imports; Exports; NAFTA; Mexico; Direktinvestition; Außenhandelsliberalisierung; Exporthandel; Importhandel; Mexiko; NAFTA-Staaten